2020
DOI: 10.1155/2020/7212037
|View full text |Cite
|
Sign up to set email alerts
|

Allergic Rhinitis and Its Epidemiological Distribution in Syria: A High Prevalence and Additional Risks in War Time

Abstract: Background. Allergic rhinitis (AR) is a global disease that affects a huge proportion of people around the world especially in the Middle East, where multiple allergy-promoting factors can be found. Although AR is not fatal, it severely affects the quality of life. However, it is usually overlooked in developing countries due to resource scarcity. Methods. An online questionnaire on social media was used which included demographics, smoking, socioeconomic-status (SES), war-related questions, and the score for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

5
3

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 45 publications
0
33
0
Order By: Relevance
“…As more than half of this study had at least one positive war variable and even higher prevalence of war variables were found in many studies of the Syrian population and that this exposure had many ramifications to different health aspects [4,6,8,9,11,12].…”
Section: Ptsdmentioning
confidence: 63%
See 1 more Smart Citation
“…As more than half of this study had at least one positive war variable and even higher prevalence of war variables were found in many studies of the Syrian population and that this exposure had many ramifications to different health aspects [4,6,8,9,11,12].…”
Section: Ptsdmentioning
confidence: 63%
“…Furthermore, PTSD sufferers may develop somatoform complications manifesting as chronic pain, health deterioration, greater vulnerability to medical problems, and increased numbers of medical disorders [5] such as major non-malignant gastric-tract disorder [7]. Moreover, war-related distress was found to correlate with allergic rhinitis [8] and laryngopharyngeal reflux [9].…”
Section: Introductionmentioning
confidence: 99%
“…In patients with LPR, males comprised of 20.5% (CI 95%: 15.4-26.1), females comprised of 79.5% (CI 95%: 73.9-84.6), cigarette smoking comprised of 21.4% (CI 95%: 16.2-26.9) shisha smoking comprised of 33.3% (CI 95%: 27.4-39.7), subjects with asthma comprised of 4.3% (CI 95%: 2.1-7.3), and subjects with allergic reactions comprised of 8.1% (CI 95%: 4. [7][8][9][10][11][12].…”
Section: Resultsmentioning
confidence: 99%
“…The high prevalence of smoking may be a factor of the high prevalence of LPR in Syria (9), mainly that there are no strong regulations to prevent smoking, causing a high exposure to second-hand smoking which could not be measured in our study. Another theory is that as allergic rhinitis is very common in Syria (11), and that allergic rhinitis and LPR may be correlated (24) which could explain this nding. We also speculate that the high psychological stress that Syrians face with high prevalence of severe mental disorder from war (12), this could cause dyspepsia and exaggerating of GORD symptoms which can mimic LPR.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies In Syria found that dental and genitival health deteriorated more in patients with PTSD and mental disorders (44)(45)(46). Another study found around 50% of the population had allergic rhinitis which could be from the indirect or direct effects of war or the unique environment (47). Smoking is also common among the Syrian population, mainly social shisha smoking which could a methods to get away from the daily stress, mainly among university students (48).…”
Section: Outcomes Of the Psychological Burdenmentioning
confidence: 99%